Adsorption of phenol on gold as studied by capacitance and reflectancen measurements - Lezna, Reynaldo Oscar (1991)
Adsorption of phenol on a polycrystalline gold electrode has been studied by capacitance and modulated reflectance measurements. Two main processes were detected. First, an adsorption-desorption peak was observed at negative charge on the electrode which was related to a flat configuration of the molecule bonded to the surface through its ir system. In this case the interactions between adsorbed phenol and the electrode are not strong enough to modify the intrinsic optical properties of the metal. A second capacitive peak, detected over a region of positive charge on the metal, was found to show hysteresis and, besides, it distorts the electroreflectance effect of gold to such an extent that separation of the optical effects of charge and coverage was not possible. This behavior, typical of the formation of strong covalent bonds, was associated with the reorientation of the molecule from flat to vertically attached to the metal by means of its oxygen atom.